Pregnane X receptor activation remodels glucose metabolism to promote NAFLD development in obese mice - Mikko Karpale; Outi Kummu; Olli Kärkkäinen; Marko Lehtonen; Juha Näpänkangas; Uta M. Herfurth; Albert Braeuning; Jaana Rysä; Jukka Hakkola (Elsevier, 2023)
Objective: Both obesity and exposure to chemicals may induce non-alcoholic fatty liver disease (NAFLD). Pregnane X Receptor (PXR) is a central target of metabolism disrupting chemicals and disturbs hepatic glucose and lipid metabolism. We hypothesized that the metabolic consequences of PXR activation may be modified by existing obesity and associated metabolic dysfunction. Methods: Wildtype and PXR knockout male mice were fed high-fat diet to induce obesity and metabolic dysfunction. PXR was activated with pregnenolone-16α-carbonitrile. Glucose metabolism, hepatosteatosis, insulin signaling, glucose uptake, liver glycogen, plasma and liver metabolomics, and liver, white adipose tissue, and muscle transcriptomics were investigated. Results: PXR activation aggravated obesity-induced liver steatosis by promoting lipogenesis and inhibiting fatty acid disposal. Accordingly, hepatic insulin sensitivity was impaired and circulating alanine aminotransferase level increased. Lipid synthesis was facilitated by increased liver glucose uptake and utilization of glycogen reserves resulting in dissociation of hepatosteatosis and hepatic insulin resistance from the systemic glucose tolerance and insulin sensitivity. Furthermore, glucagon-induced hepatic glucose production was impaired. PXR deficiency did not protect from the metabolic manifestations of obesity, but the liver transcriptomics and metabolomics profiling suggest diminished activation of inflammation and less prominent changes in the overall metabolite profile. Conclusions: Obesity and PXR activation by chemical exposure have a synergistic effect on NAFLD development. To support liver fat accumulation the PXR activation reorganizes glucose metabolism that seemingly improves systemic glucose metabolism. This implies that obese individuals, already predisposed to metabolic diseases, may be more susceptible to harmful metabolic effects of PXR-activating drugs and environmental chemicals.